2017
DOI: 10.3389/fncel.2017.00187
|View full text |Cite
|
Sign up to set email alerts
|

The Hyperpolarization-Activated Current Determines Synaptic Excitability, Calcium Activity and Specific Viability of Substantia Nigra Dopaminergic Neurons

Abstract: Differential vulnerability between Substantia Nigra pars compacta (SNpc) and Ventral Tegmental Area (VTA) dopaminergic (DAergic) neurons is a hallmark of Parkinson’s disease (PD). Understanding the molecular bases of this key histopathological aspect would foster the development of much-needed disease-modifying therapies. Non-heterogeneous DAergic degeneration is present in both toxin-based and genetic animal models, suggesting that cellular specificity, rather than causing factors, constitutes the background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…It is worth noting that unilateral ZD7288 injection into the SNc of adult rats prominently increased the number of apomorphine-induced rotations and reduced the immunofluorescence intensity of tyrosine hydroxylase-positive neurons. These effects were not observed in VTA neurons (Carbone et al, 2017).…”
Section: Hcn Channels May Be An Ion Channel Mechanism Underlying the mentioning
confidence: 86%
See 1 more Smart Citation
“…It is worth noting that unilateral ZD7288 injection into the SNc of adult rats prominently increased the number of apomorphine-induced rotations and reduced the immunofluorescence intensity of tyrosine hydroxylase-positive neurons. These effects were not observed in VTA neurons (Carbone et al, 2017).…”
Section: Hcn Channels May Be An Ion Channel Mechanism Underlying the mentioning
confidence: 86%
“…Direct pharmacological suppression of I h through ZD7288 (50 μM) also increased the decay time and amplitude of eEPSPs, and this response was more prominent in SNc than in VTA neurons (Masi et al, 2015). ZD7288 also significantly reduced the amplitude of evoked inhibitory post-synaptic potentials (eIPSPs) (Carbone et al, 2017). Therefore, I h blockage likely enhances synaptic excitability through a dual mechanism in SNc dopaminergic neurons, specifically, by potentiating excitatory inputs and weakening inhibitory inputs.…”
Section: Hcn Channels May Be An Ion Channel Mechanism Underlying the mentioning
confidence: 99%
“…Because no association between HCN mutations and PD have been discovered so far, it remains to be determined whether HCN LOF participates in the pathogenic cascade of clinical PD and how genetic or sporadic PD-triggers induce HCN LOF. In this respect, it was demonstrated the HCN current is negatively modulated by acute inhibition of mitochondrial ATP production, an effect resembling that induced by low intracellular cAMP [53]. It is plausible that metabolic stress and reduced ATP production result in reduced cAMP synthesis in preclinical stages of PD.…”
Section: Parkinson's Diseasementioning
confidence: 94%
“…Furthermore, the electrophysiological effects exerted by pharmacological inhibition of HCN current, as well as the ensuing somatic Ca 2+ inflow, is larger in vulnerable SNc as compared to resistant VTA DAergic neurons [52]. Finally, it was shown that chronic inhibition of HCN current attained with local administration of two distinct HCN blockers, causes DAergic neuronal death in the SNc, but not in the VTA, of normal adult rats [53]. Based on their results, the authors speculate that HCN current may undergo loss of function (LOF) during the early phases of disease progression, possibly as a consequence of metabolic fatigue, and drive Ca 2+ -mediated toxicity, thus representing an SNcspecific pathogenic pathway.…”
Section: Parkinson's Diseasementioning
confidence: 97%
See 1 more Smart Citation